Invadopodia in context - Bergman, Aviv (Landes Bioscience, 2014)
Invadopodia are dynamic protrusions in motile tumor cells whose function is to degrade extracellular matrix so that cells can enter into new environments. Invadopodia are specifically identified by microscopy as proteolytic invasive protrusions containing TKS5 and cortactin. The increasing complexity in models for the study of invadopodia, including engineered 3D environments, explants, or animal models in vivo, entails a higher level of microenvironment complexity as well as cancer cell heterogeneity. Such experimental setups are rich in information and offer the possibility of contextualizing invadopodia and other motility-related structures. That is, they hold the promise of revealing more realistic microenvironmental conditions under which the invadopodium assembles and functions or in which tumor cells switch to a different cellular phenotype (focal adhesion, lamellipodia, proliferation, and apoptosis). For such an effort, we need a systemic approach to microscopy, which will integrate information from multiple modalities. While the individual technologies needed to achieve this are mostly available, data integration and standardization is not a trivial process. In a systems microscopy approach, microscopy is used to extract information on cell phenotypes and the microenvironment while -omics technologies assess profiles of cancer cell and microenvironment genetic, transcription, translation, and protein makeups. Data are classified and linked via in silico modeling (including statistical and mathematical models and bioinformatics). Computational considerations create predictions to be validated experimentally by perturbing the system through use of genetic manipulations and molecular biology. With such a holistic approach, a deeper understanding of function of invadopodia in vivo will be reached, opening the potential for personalized diagnostics and therapies.